Synthesis, properties and conformational studies of anti-8-fluoro-16-methyl-[22]metacyclophane and anti-8-fluoro-16-methyl[22]metacyclophane-1,9-diene - Lai, Y.-H. (2014)
Journal of the Chemical Society, Perkin Transactions 1